Multi-view-based cooperative observation method for space non-cooperative target's attitude determination (Xibei Gongye Daxue Xuebao, 2021)
The parameter identification of a non-cooperative target is a key problem of on-orbit servicing. Due to poor priori information about the motion and structure of non-cooperative targets, the traditional cooperative estimation architecture is inadequate. In addition, the existing method based on single observation spacecraft is difficult to ensure a good observation state for a long time. This paper proposes a method for observing and estimating attitude kinematic state of a non-cooperative space target based on multi-spacecrafts cooperative observation. The space target's 3D point cloud data is reconstructed based on the data with different viewpoints. The target's attitude change is calculated based on the 3D point cloud matching, and the kinematics information is estimated via EKF filtering. The simulation results demonstrate the efficiency of the proposed approach. As the proposed method does not require priori model, structural information or accurate motion information of the tumbling non-cooperative target, it can avoid the influence of occlusion or date missing in space observation, it is suitable for space on-orbit servicing with non-cooperative target in future.